Combinations, Contradictions, And Cross Fertilization in Actor Network Theory and Assemblage Thinking (International Journal of Innovative Research in Computer Science & Technology, 2021)
This paper shows that assembling  thought as well as actor-network theory (ANT) have such  a great deal in common than the debate suggests. It  proposes three cross-fertilizations depending on  intersections as well as disjunctions among the two  techniques, with implications for comprehending three  key socio-material processes: stability, transformation, as  well as affect. To begin with, ANT's conceptual language  may aid assemblage thinking by offering a spatial  account of how aggregates are brought collectively,  extended over space, and stabilize. Secondly, each  technique is better adapted to thinking about a certain  type of variation in socio-material interactions: ANT  depicts change without rupture (fluidity), whereas  assemblage thinking depicts change with rupture (events).  Finally, assemblages thought has the ability to instil in  ANT a greater understanding of affect's generative role in  the construction of socio-material links through the  establishment of desire/wish. We demonstrate the  implications of this cross-fertilization for empirical  studies through a case study of the global market for  assisted reproduction.
Keywords: Assemblage; Actor-Network Theory; Cross-Fertilization; Fertilization; Socio-Material